GEOGRAFI DIALEK BAHASA SALUAN - Valantino Ateng Pamolango (Universitas 17 Agustus 1945 Surabaya, 2012)
Abstrak. This article explores the dialectology of Saluan language. There are 24vowelphonemes, but only2vowels and 5consonantsvariants arescatteredin the districts ofPagimana, Lobuand Bualemo, such as/a/and/e/, /Ê”/and/k/, /l/and/n/and/r/and/l/. Thedistributionof the lexicalvariations is also diverse, such as the distribution between districts, then the spread between two districts, and a random distribution in each district. Both thephonologicalandlexicaldistributionsindicatethat thedifferencesthat occurinspoken Saluanis still great. ThusSaluanlanguagecan be maintainedas aliving regional languageand has not yet shown any indication towards extinction.Furtherstudiesonthis languagealsoneeds to be done, especiallyin theother areas oflinguistics.Â Kata kunci: Saluanlanguage, dialect geography, dialectometry,Â